2021
DOI: 10.1002/ppul.25720
|View full text |Cite
|
Sign up to set email alerts
|

Fluid overload in children with pediatric acute respiratory distress syndrome: A retrospective cohort study

Abstract: Objectives: To assess the association of cumulative fluid overload (FO) up to 14 days from the diagnosis of pediatric acute respiratory syndrome (PARDS) with pediatric intensive care unit (PICU) mortality, 28-day mechanical ventilation free days (VFD), and 28-day intensive care unit free days (IFD). We hypothesized that fluid overload, even beyond the acute period, would be associated with increased morbidity and mortality.Methods: We conducted a retrospective cohort study of PARDS patients admitted to PICU fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The goal of fluid resuscitation in PARDS is to maintain adequate intravascular volume to maintain optimal Do 2 and end-organ perfusion (56)(57)(58). However, increasing evidence has shown that excessive positive cumulative fluid balance (CFB) and fluid overload have been associated with increased mortality and morbidity (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Observational studies have shown that fluid overload greater than 20% in children with ARDS is associated with increased oxygenation indices, duration of MV, and PICU LOS (60), while other observational studies have identified positive fluid balance at day three to be associated with increased morbidity (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of fluid resuscitation in PARDS is to maintain adequate intravascular volume to maintain optimal Do 2 and end-organ perfusion (56)(57)(58). However, increasing evidence has shown that excessive positive cumulative fluid balance (CFB) and fluid overload have been associated with increased mortality and morbidity (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Observational studies have shown that fluid overload greater than 20% in children with ARDS is associated with increased oxygenation indices, duration of MV, and PICU LOS (60), while other observational studies have identified positive fluid balance at day three to be associated with increased morbidity (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Justificationmentioning
confidence: 99%
“…However, increasing evidence has shown that excessive positive cumulative fluid balance (CFB) and fluid overload have been associated with increased mortality and morbidity (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Observational studies have shown that fluid overload greater than 20% in children with ARDS is associated with increased oxygenation indices, duration of MV, and PICU LOS (60), while other observational studies have identified positive fluid balance at day three to be associated with increased morbidity (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). In a quasi-RCT performed in children with PARDS, a preemptive fluid strategy (PFS) bundle was implemented, which aimed at maintaining adequate intravascular volume while minimizing fluid overload.…”
Section: Justificationmentioning
confidence: 99%
“…The tissue edema, which may co-exist with both hyperand hypovolemic intravascular volume, is considered to be the main cause of adverse effects of fluid overload. This could explain the consistent finding that positive cumulative fluid balance is associated with poor outcomes in both critically ill adults and children (3,7,(14)(15)(16)(17)(18)(19)(20). **Other: switch to enteral feeding (N = 1, 1.2%), not further specified (N = 1, 1.2%).…”
Section: Discussionmentioning
confidence: 97%
“…Peak chronic fluid overload was linked to lower ventilation free days and intensive unit free days, and the rate to peak chronic fluid overload throughout the first 14 days of paediatric acute respiratory distress was linked to death. 7 Findings of another retrospective cohort study revealed that 132 (18%) participants died while non-survivors showed greater overall fluid balance beginning on day 3 as per the unadjusted analyses. A positive overall fluid balance on days 5 through 7 was linked, in a multivariable analysis, to higher mortality.…”
Section: Evidence From Literature For Adverse Effects Of Fluid Overloadmentioning
confidence: 92%